The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1179/1743284712y.0000000194
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of retained austenite in Cr–Ni weld metals at low temperatures

Abstract: As environmental temperature decreases, the amount of retained austenite is more likely to greatly reduce due to the thermal austenite-martensite transformation caused by the decreased thermal stability of retained austenite, probably making its amount lower than the required content. In the present study, the thermal stability of retained austenite in Cr-Ni weld metals was investigated to see whether sufficient retained austenite can be maintained at low temperatures. The specific experimental procedure is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…When applied strain imposes on it, it will transform into martensite. As an accompanied research of the present study, the mechanical 16) and thermal stability 16) of the retained austenite have been investigated in detail. It has been shown that the retained austenite enhances the tensile properties 11, 12) and fracture toughness 13) through the strain-induced marteniste transformation from it.…”
Section: The Effect Of Retained Austenite On the Impact Behavior At V...mentioning
confidence: 99%
“…When applied strain imposes on it, it will transform into martensite. As an accompanied research of the present study, the mechanical 16) and thermal stability 16) of the retained austenite have been investigated in detail. It has been shown that the retained austenite enhances the tensile properties 11, 12) and fracture toughness 13) through the strain-induced marteniste transformation from it.…”
Section: The Effect Of Retained Austenite On the Impact Behavior At V...mentioning
confidence: 99%
“…The thermal stability of retained austenite in the Cr-Ni weld metal has been investigated elsewhere. 12) It was found that if the initial content of retained austenite is less than 20%, even if the service temperature reduces from 25 C to −196 C, its amount remains constant. This demonstrates that within the temperature range of 25 C to −196 C, temperature variation does not affect the amount of retained austenite when its initial amount is less than 20%.…”
Section: Introductionmentioning
confidence: 99%